Pengembangan kegemaran membaca di perpustakaan sekolah melalui pembinaan komunitas cinta membaca untuk mewujudkan generasi yang literate - Arsidi, Arsidi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2014)
Reading is the most problem that this nation challenge with. Nowadays, as the ICT involved any pace of human life, many libraries are getting the same problem that is how to attract people to love reading, or accessing information in general. Many actions were taken by some libraries to attract people to love reading, for instance, a Love Reading Community (Komunitas Cinta Membaca). This is one of solutions that can be adopted to other libraries. The aim of this community is to encourage students having reading habits. Therefore, the paper will discuss the community efforts in encouraging student to love reading.